Taxonomic Status of Three Types of Fejervarya cancrivora from Indonesia and Other Asian Countries Based on Morphological Observations and Crossing Experiments - Kurniawan, N.; Djong, T.H.; Islam, M.M.; Nishizawa, T.; Belabut, D.M.; Yong, Hoi Sen; Yasir, I.; Sumida, M. (Zoological Society of Japan, 2011)
Although the crab-eating frog Fejervarya cancrivora is one of the most widely distributed species in Asian region, taxonomic relationships among different populations remain unclarified. In this study, we attempted to elucidate the taxonomic status of F. cancrivora from Indonesian and other Asian populations. Five populations of F. cancrivora from Selangor (Malaysia), Cianjur (Java, Indonesia), Trat (Thailand), Khulna (Bangladesh), and Makassar (Sulawesi, Indonesia) were morphologically observed and subjected to crossing experiments. Principal component and clustering analyses revealed that these five populations could be organized into three groups corresponding to three observed morphological types: a Selangor and Cianjur group (large-type), a Trat and Khulna group (mangrove-type), and a Makassar group (Sulawesi-type). The limited crossing experiments revealed that hybrids between Selangor females and Cianjur and Trat males developed normally, whereas hybrids between Selangor females and Khulna males showed incomplete gametic isolation. Histological observations of the testes of mature males revealed the presence of pycnotic nuclei in the hybrids between Selangor females and Khulna males in addition to normal bundles of spermatozoa. In contrast, no pycnotic nuclei were observed in the Selangor controls. Although meiotic metaphases in the controls were normal, those in hybrids showed several abnormalities, such as the appearance of univalents and an increase in rod-shaped bivalents. Based on our findings from the morphological observations and crossing experiments, we conclude that each of three identified types represents a distinct species. We propose that the large-type is F. cancrivora, the mangrove-type is F. moodiei, and the Sulawesi-type represents an undescribed species.